2013
DOI: 10.1002/maco.201307456
|View full text |Cite
|
Sign up to set email alerts
|

Performance of superheater materials in simulated oxyfuel combustion conditions

Abstract: Oxyfuel fired combustion has the potential to increase the fireside corrosion rates comparing to air firing combustion as a result of the increasing amounts of aggressive combustion products due to recycling of flue gas. The changes in the combustion gas chemistry will also affect the chemistry and formation of deposits, with potentially increasing corrosion and internal attack of the boiler components that are in contact with the combustion and flue gas environment. As the currently available information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nowadays, the energy industry is betting on energy generation methods with low or zero net greenhouse gas emissions. [ 1,2 ] Among the different strategies proposed to achieve this objective, replacement of fossil fuels by biomass in co‐firing power plants is of growing interest [ 3,4 ] because biomass is considered as a carbon‐neutral fuel. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the energy industry is betting on energy generation methods with low or zero net greenhouse gas emissions. [ 1,2 ] Among the different strategies proposed to achieve this objective, replacement of fossil fuels by biomass in co‐firing power plants is of growing interest [ 3,4 ] because biomass is considered as a carbon‐neutral fuel. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the energy industry is betting on energy generation methods with low or zero net greenhouse gas emissions. [1,2] Among the different strategies proposed to achieve this objective, replacement of fossil fuels by biomass in co-firing power plants is of growing interest [3,4] because biomass is considered as a carbon-neutral fuel. [5] Some of the main problems that arise when working with biomass at high temperatures in co-firing power plants are: (i) The high presence of aggressive elements and (ii) the great heterogeneity because of the continuous changes of these aggressive media.…”
Section: Introductionmentioning
confidence: 99%
“…The change in flue gas composition has prompted many researchers to study afresh the fireside corrosion of boiler tube materials in simulated oxyfuel environment [1][2][3][5][6][7]. However, most of these studies have been carried out by exposing samples to single-environment of flue gas.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focused on the comparison of materials and corrosive environments. 3,[6][7][8][9][10][11][12][13][14] Simms carried out the laboratory based fireside corrosion tests on superheater/re-heater materials in oxy-firing combustion conditions. Results showed that the metal damage was reduced when the amount of Cr in the alloys was increased (metal damage: T92.347HFG.HR3C.625).…”
Section: Introductionmentioning
confidence: 99%